PRISON ESCAPE VIEWED FROM ISLAMIC LAW PERSPECTIVES (A Case Study at Muara Labuh Prison) - Salma Salma; Riki Hamdi; Taufik Hidayat (Arena Hukum, 2023)
In Indonesia, there have been numerous cases of people escaping from prison including the Muara Labuh Prison. This research analyze the prison conditions, the cases that occurred there, the motives behind the escape, the responsibility of the warden, and how Islamic law views escape. Data were collected through observation of prison conditions and interviews. Data analysis was performed in several stages, including data reduction, display, and verification techniques, then, narrated using a qualitative approach and Islamic law. The results revealed three cases of inmates escaping from this prison. They have a variety of reasons for this, including an inability to restrain sexual desires, being unable to serve very long sentences, depression, and poor prison security, which is the warden's responsibility. Prison escape is not justified in Islamic law due to the necessity to obey state rules that are not specifically regulated in the Qur'an and Sunnah.